SINERGI FIKIH DAN ILMU FALAK: ANALISIS KRITIS LARANGAN BUANG HAJAT MENGHADAP KIBLAT - Said, Musdalifah; Akmal, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract This study aims to analyze the nature of the prohibition on defecating facing or facing away from the Qibla normatively, identify its urgency in the formation of character and spatial orientation of Muslims, and explore its multidimensional wisdom through the approach of astronomy and modern science. The method used is qualitative library research with data sources from classical fiqh literature, hadith, and scientific astronomy journals. The data is analyzed descriptively and analytically by integrating Islamic law approaches and astronomical calculations (spherical trigonometry and the WGS-84 geodetic model). The results of the study indicate that: First, this prohibition is based on authentic hadith as a form of ta'zhim al-qiblah (respect for the Qibla), where the majority of scholars agree that it is haram in open spaces (fadha') and provide leniency (rukhsah) in buildings with barriers. Second, spiritually and technically, this provision functions as an instrument for character formation and awareness of spatial orientation (spatial awareness), as well as being a guide for modern architecture in balancing normative texts with the reality of building design. Third, from an astronomical perspective, this prohibition encourages the integration of Islamic jurisprudence (fiqh) and science through the use of GPS technology and the ellipsoidal Earth model for directional accuracy. This aligns with the Maqasid al-Shariah values ​​of protecting reason and the environment, transforming ritual observance into an applicable scientific understanding.